Training medical students in participatory rural appraisal methods using ADDIE framework - Saurabh RamBihariLal Shrivastava; Gandes Retno Rahayu; Titi Savitri Prihatiningsih (Journal of Education and Health Promotion)
Participatory rural appraisal (PRA) methods have a special place in improving the health and well-being of the rural population. In the global vision to deliver contextual medical education to benefit the local population, exposure of medical students to participatory rural appraisal methods plays a vital role. However, all these benefits can only materialize, once we systematically plan and execute the training of medical students, and this essentially requires the adoption of an instructional design. Analyze-Design-Development-Implementation-Evaluation (ADDIE) is one of the most frequently used instructional designs in the field of medical education, owing to its simplicity. To conclude, participatory rural appraisal methods carry immense significance in the delivery of contextual medical education and in improving the health standards of the local population. The ADDIE instructional design is an effective approach to planning and conducting training of medical students on PRA methods.